Remediation of heavy metals by native plant species grown in Iran’s richest gold mine and study of plants’ pollution tolerance strategies - Torbati, Samaneh; Esmailbegi Kermani, Shokouh; Abedini, Ali (Frontiers in Earth Science, 2024)
Mining is defined as an environmentally hazardous activity and discharges metals and other elements to environment. Bioremediation is a natural and sustainable technique for harnessing the potential of microorganisms and plants to remove, degrade or stabilize pollutants from contaminated sites and cleanup and restoration of the environment. In the present study, following the investigation of heavy metals pollution in the soil samples collected from the Zarshuran mining area, the role of twenty native plant species in the bioaccumulation of heavy metals was evaluated. After preparation of soil and plant samples, inductively coupled plasma-mass spectroscopy (ICP-MS) was used to determine the concentrations of elements in the soil and plant samples. It was confirmed that the soil samples were highly contaminated by silver (Ag), zinc (Zn), cadmium (Cd), lead (Pb), and antimony (Sb). High amounts of Pb and Zn were accumulated in Eryngium billardieri and Astragalus rostratus. Further, these two plant species could uptake, transport and accumulate Ag in their aerial parts and the enrichment coefficient of their shoots was more than 1. Scorzonera latifolia had also good potential to stabilise Ag, Zn and Pb in its root. As a result, E. billardieri, A. rostratus and S. latifolia may be suitable candidate species for cleanup soils from the heavy metals in contaminated sites. Overall, augmentation of superoxide dismutase activity and the amounts of total phenols and flavonoids in different parts of E. billardieri and A. rostratus confirmed the induction of antioxidant defense systems in the plants (compared to the control plants) and an attempt by the plants to tolerate heavy metals pollution.